2015
DOI: 10.1007/s40618-015-0312-9
|View full text |Cite
|
Sign up to set email alerts
|

Prader-Willi syndrome: a review of clinical, genetic, and endocrine findings

Abstract: IntroductionPrader-Willi syndrome (PWS) is a multisystemic complex genetic disorder caused by lack of expression of genes on the paternally inherited chromosome 15q11.2-q13 region. There are three main genetic subtypes in PWS: paternal 15q11-q13 deletion (65–75 % of cases), maternal uniparental disomy 15 (20–30 % of cases), and imprinting defect (1–3 %). DNA methylation analysis is the only technique that will diagnose PWS in all three molecular genetic classes and differentiate PWS from Angelman syndrome. Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
514
3
19

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 533 publications
(540 citation statements)
references
References 144 publications
(164 reference statements)
4
514
3
19
Order By: Relevance
“…IGF-I values above the reference range increased in the cohort from 19% to 37% and 36% after 1, 2 and 3 years of GHT respectively. This percentage is still of some concern as elevated IGF-I levels may contribute to lymphoid hyperplasia and associated OSA in young children after commencing GHT [32]. However, the percentage of children with elevated IGF-I levels was considerably less when compared to other studies using a higher dose of 7 mg/m 2 /week, in which the majority of children had an IGF-I level over 2 SDS after 2 or more years of treatment [29,33] despite a similar linear growth response.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…IGF-I values above the reference range increased in the cohort from 19% to 37% and 36% after 1, 2 and 3 years of GHT respectively. This percentage is still of some concern as elevated IGF-I levels may contribute to lymphoid hyperplasia and associated OSA in young children after commencing GHT [32]. However, the percentage of children with elevated IGF-I levels was considerably less when compared to other studies using a higher dose of 7 mg/m 2 /week, in which the majority of children had an IGF-I level over 2 SDS after 2 or more years of treatment [29,33] despite a similar linear growth response.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Absence of reaction to noxious or painful stimuli Autosomal recessive disease caused by a mutation in tRKA gene located on chromosome 1 (1q21-q22) encoding the highaffinity tyrosine kinase receptor NTRK1 for nerve growth factor (NGF) 7 , whereas a high pain threshold is a very common symptom in Prader-Willi syndrome, its sister syndrome 8 . Other authors observed a high pain tolerance in 86% of children with chromosome 15q duplication syndrome 9 , and this clinical features is more evident in case of isodicentric mutations rather than in the interstitial forms in which the load of duplicate genes is less.…”
Section: Disorders Other Than Channelopathiesmentioning
confidence: 99%
“…Como dificultades presentes a lo largo del ciclo vital de los sujetos con SPW destacan: hipotonía, baja estatura, hiperfagia, discapacidad cognitiva, así como diversos problemas conductuales. El fenotipo, posiblemente, esté causado por disfunción hipotalámica, siendo responsable de la hiperfagia, hipersomnia y de múltiples anormalidades endocrinas, incluyendo déficits en el crecimiento de la hormona estimuladora del tiroides, hipogonadismo e insuficiencia adrenal central 14 .…”
Section: El Síndrome De Prader-willi (Spw)unclassified